Nonlinear Dynamic Characteristics of Multidisk Rod Fastening Rotor with Axial Unbalance Mass Distribution - Li Zhao; Haosui Zhang; Yibing Liu; Chao Zhou (Shock and Vibration)
During long-term operation, the blades of rod fastening rotor are very prone to fault and may cause uneven axial mass distribution. The dynamic characteristics of a multidisk rod fastening rotor with axial unbalance mass distribution are studied. A four-disk rod fastening rotor model was established by the lumped mass method. The mass unbalance on different disks was used to simulate blade faults in different parts, and nonlinear factors such as oil film force and disk contact effect were considered. The fourth-order Runge-Kutta method was used to solve the model, and the spectrum and axis trajectory curves were obtained. The influence of fault location and rotating speed on rotor dynamic characteristics was analysed when there were blade faults on two disks. The results show that a large, unbalanced mass will bring strong nonlinear characteristics. The rod fastening rotor may be in different motion states at different rotating speeds. When the fault position of two disks changes, the changes of bearing spectrum, axis trajectory, and phase difference have regularity. The results can provide a theoretical basis for condition monitoring and fault diagnosis of rod fastening rotor.